2013
DOI: 10.1097/scs.0b013e31828dce28
|View full text |Cite
|
Sign up to set email alerts
|

Disseminating Surgery Effectively and Efficiently in Haiti

Abstract: The need for surgical care in Haiti remains vast despite the enormous relief efforts after the earthquake in 2010. As the poorest country in the Western hemisphere, Haiti lacks the necessary infrastructure to provide surgical care to its inhabitants. In light of this, a multidisciplinary approach led by Partners In Health and Dartmouth-Hitchcock Medical Center is improving the access to surgical care and offering treatment of a broad spectrum of pathology. This article discusses how postearthquake Haiti partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Many studies reported different strategies to improve the quality of medical services around the world, especially in developing countries. [20][21][22][23][24][25][26][27][28][29][30][31][32] Economic, cultural, and geographical reasons usually limit the access to specialized health centers in developing countries, especially in rural areas. [1][2][3] In addition, most of the developing countries have a very centralized health system that concentrates a high number of patients in few hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported different strategies to improve the quality of medical services around the world, especially in developing countries. [20][21][22][23][24][25][26][27][28][29][30][31][32] Economic, cultural, and geographical reasons usually limit the access to specialized health centers in developing countries, especially in rural areas. [1][2][3] In addition, most of the developing countries have a very centralized health system that concentrates a high number of patients in few hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…While the full extent of injuries sustained in the earthquake remains unknown, initial reports suggested at least 12,000 people were injured in the immediate earthquake [ 1 ], including a significant number of limb injuries requiring orthopaedic surgical management [ 2 ]. There are three options for receiving surgical treatment in Haiti: public hospitals, private hospitals in metropolitan areas that require a financial contribution, and charitable hospitals [ 4 ]. Proper surgical management of orthopaedic injuries often necessitates intraoperative imaging via a C-arm machine (C-arm).…”
Section: Introductionmentioning
confidence: 99%